(untitled) (Southwestern Research Journal, 2024)
There have been significant effects on the academic and economic structures of Nepal as a result of the exodus of students choosing to pursue higher education overseas. This systematic assessment aims to examine the underlying causes of Nepalese students’ propensity to study overseas and assess the impact of that decision on the country’s educational authority, particularly about acceptance and competition rates at universities. Using the PRISMA approach, the study collated qualitative and quantitative literature published between 2017 and 2023 based on the migration of international students, push and pull forces, and their effects on domestic education systems. One of the main incentives for Nepalese students to travel abroad for further education is the availability of top-notch international degrees, better career possibilities, and improved educational standards. Outmigration has resulted in a substantial decline in enrolment in public universities, a decline in academic achievement, and a worsening of the brain drain, particularly in the fields of teaching, information technology, and healthcare. The report also identifies systemic issues that are present in local institutions and that contribute to this mass departure, such as a lack of funding or academic infrastructure. Despite significant efforts to reform, the Nepalese academic system continues to confront obstacles because of the country’s strong interest in international studies, which limits innovation in higher education and impedes development initiatives.